Current possibilities and challenges of using metaverse-like environments and technologies in education - Bakk, Ágnes Karolina; Bényei, Judit; Ballack, Paul; Parente, Fernanda (Frontiers in Virtual Reality, 2025)
This paper presents findings from a stakeholder mapping exercise exploring how higher education professionals perceive and engage with metaverse‐like environments and technologies. Based on 20 in‐depth, semi‐structured interviews with higher education professionals, the research investigates both the perceived opportunities and challenges associated with implementing metaverse-related tools in academic contexts. The results present various viewpoints: while some participants highlight that these environments are valuable for experiential learning, others mention such barriers as institutional limitations and insufficient technological infrastructure. The study contributes to the discussion on the role of virtual environments in higher education, emphasizing the importance of strategic support and pedagogical alignment for meaningful integration.